The Influence of Structural Design on the Hydrodynamics of Floating Offshore Wind Turbine Platforms - Nilotpal Dhar; Charlie J. Lloyd; John Walker; Robert M. Dorrell (Journal of Marine Science and Engineering, 2025)
Floating offshore wind turbine (FOWT) platforms are subject to a wide range of hydrodynamic loading and dynamic movement, making hydrodynamic force evaluation difficult. Amongst various floating platforms, submersible platforms are structurally complex, with multiple members held together by cross-braces. The influence of these members on hydrodynamic loading is poorly understood. An investigation of the effect of these members on loads is essential to optimise the design of FOWT platforms, mooring systems, and protective coatings, leading to a reduction in construction and maintenance costs. This paper numerically investigates the effect of structural members on the forces acting on a static semi-submersible platform in a unidirectional current flow of Reynolds number (<semantics>Re</semantics>) ranging from 2000 to 200,000, based on structural diameter and tidal velocity. The OC4 semi-submersible is chosen as the baseline platform. For each <semantics>Re</semantics>, this study is divided into three stages, such that in each stage, the number of members increased. These stages are as follows: (1) a finite cylinder (FC), (2) a finite cylinder with a heave plate (FCHP), (3) three cylinders with heave plates (TCHP) in an equilateral triangle arrangement, and (4) the OC4 semi-sub. The drag coefficient (<semantics><mover>C¯</mover>d</semantics>) increases with increasing structural members and weakly varies with increasing <semantics>Re</semantics>. However, the viscous drag coefficient (<semantics><mover>C¯</mover>f</semantics>) decreases with increasing <semantics>Re</semantics>, and a reverse trend is seen in the case of the pressure drag coefficient (<semantics><mover>C¯</mover>p</semantics>), with pressure drag dominating over friction drag. Further, the contribution of individual members is observed to vary with <semantics>Re</semantics>. The contribution of cylinders towards <semantics><mover>C¯</mover>d</semantics> is higher than heave plates, showing that contributions directly depend on the aspect ratio of members. In the case of TCHP and OC4, the contribution of the rear members is higher than that of the leading members due to the strong wake effect of the former. Also, the braces and pontoons of OC4 have contributed substantially towards total <semantics><mover>C¯</mover>d</semantics>, unlike the central cylinder, which has experienced low drag due to the wake effect of the front cylinder and heave plate. Also, flow visualisation has shown vortex cores, and recirculating flows in the near wake of the cylinders and under the heave plates. Recirculation zones under the heave plates lead to vertical pressure on the structures. This vertical pressure increases with the number of structural members and the vertical pressure coefficient (<semantics><mover>C¯</mover>v</semantics>), varying with <semantics>Re</semantics> due to three-dimensionality in the wake. Further, this pressure varies across the bottom surfaces of structures. Analyses of the streamwise pressure coefficient have shown it is highest on the front surfaces of cylinders. The highest friction is on the top and sides of the heave plates, and there is considerable friction on the sides of the cylinder.